THE EFFECTIVENESS OF 5K-BASED SYNECTIC MODEL TO IMPROVE HIGHER ORDER THINKING SKILL OF ELEMENTARY SCHOOL STUDENTS - Uswatun - Hasanah; Fahrurrozi - Fahrurrozi; Zulela M. S.; Ahmad Januar (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2021)
This study aims to analyze the effectiveness of the 5K-based Synectic model to improve the higher-order thinking skills of elementary school students. The type of research method used is a quantitative method with a quasi-experimental design and a one-group pretest-posttest design with a control group design. The sample used was 127 grade V elementary school students in the District of Kebayoran Lama who were selected by purposive sampling technique. The results of this study prove that the application of the 5K-based synectic model obtained a significant value so that it is effectively used in improving the higher-order thinking skills of elementary school students. This model can help students develop creative reasoning to solve problems, store new information, assist in producing writing, and explore social and disciplinary problems to improve their high-order thinking skills. This research can be used as input for education practitioners, especially teachers in developing learning that adapts to the needs of the times and can develop students' reasoning.